Laminaria tent use for dilation, extraction, and curettage leading to septic shock: a case report - A. Ferreira; V. Mongrain; L. Mardini (Journal of Medical Case Reports)
Abstract Background Laminaria tents are commonly used to aid cervical dilation in gynecological procedures, but their potential risks are not well documented in the literature. This case report describes a severe adverse outcome following their use. Case presentation A 27-year-old Caucasian woman G2P1 with a 14 + 1 weeks arrested pregnancy was consented for a dilation, extraction, and curettage. Two laminaria tents were inserted into the endocervix, and the following day the dilation and curettage was performed without immediate complications, although laminaria tents were in an unusual state of disintegration upon removal. Post-procedure, the patient developed fever and pelvic pain, and was found to have positive inflammatory markers, hypoxemic respiratory failure, and disseminated intravascular coagulation. A computed tomography scan revealed multiple septic emboli, and blood cultures grew Staphylococcus aureus. The clinical presentation and imaging suggested septic shock and multi-organ failure likely due to retained laminaria tent fragments. A diagnostic hysteroscopy followed by total abdominal hysterectomy and bilateral salpingectomy were performed, which revealed significant endometrial necrosis. The postoperative stay was complicated by diffuse alveolar hemorrhage needing intubation, and infective endocarditis. Despite prolonged antibiotic therapy and surgical intervention, the patient experienced persistent bacteremia but eventually recovered after a 26-day hospital stay. Conclusion This case report underscores the risks associated with laminaria tents, including severe infection. Although laminaria tents are typically used for short procedures, their use in this case led to catastrophic outcomes, highlighting the need for careful consideration of prophylactic measures and the potential benefits of antibiotic prophylaxis. This case report describes a patient who suffered from severe complications from laminaria tent insertion.